Bubble nucleation in a superfluid 3He-4He mixture induced by acoustic wave: Жидкий гелий - Abe, H.; Saitoh, Y.; Ueda, T.; Nomura, R.; Okuda, Y.; Burmistrov, S.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
We report the nucleation dynamics of bubbles induced by an acoustic wave pulse in 3He–4He liquid mixtures. The experiment was performed for the mixture with 3He fixed concentrations of about 4% and 25% and the pure superfluid 4He. When a pulse of 1 ms duration was applied to the mixture at the saturated vapor pressure, a spherical bubble was nucleated on the active area of a piezoelectric transducer. For the case of pure 4He, not a spherically shaped bubble, but an irregularly shaped, larger one was observed. We took pictures with a high speed CCD camera of the bubble expansion and contraction motions after the nucleation. We also investigated the temperature dependence of the bubble nucleation by changing the acoustic wave power. The results show that the nucleation and growth dynamics of a cavitation bubble depend greatly on the 3He concentration and temperature.